Review of all-inorganic perovskites and their tandem solar cells with crystalline silicon - Hongjun Wu; Zhaorui Sun; Haonan Li; Xiuhua Chen; Wenhui Ma; Shaoyuan Li; Zhengjie Chen; Fengshuo Xi (Energy Materials and Devices)
In widely studied organic–inorganic hybrid perovskites, the organic component tends to volatilize and decompose under high temperatures, oxygen, and humidity, which adversely affects the performance and longevity of the associated solar cells. In contrast, all-inorganic perovskites demonstrate superior stability under these conditions and offer photoelectric properties comparable to those of their hybrid counterparts. The potential of tandem solar cells (TSCs) made from all-inorganic perovskites is especially promising. This review is the first to address recent advancements in TSCs that use all-inorganic perovskites and crystalline silicon (c-Si), both domestically and internationally. This work provides a systematic and thorough analysis of the current challenges faced by these systems and proposes rational solutions. Additionally, we elucidate the regulatory mechanisms of all-inorganic perovskites and their TSCs when combined with c-Si, summarizing the corresponding patterns. Finally, we outline future research directions for all-inorganic perovskites and their TSCs with c-Si. This work offers valuable insights and references for the continued advancement of perovskite-based TSCs.